(untitled)
The International Conference on Islamic Economics in the 21st Century was the second international conference organized by the International Islamic University Malaysia IIUM), in cooperation with the Islamic Research and Training Institute IRTI) of the Islamic Development Bank (IDB). The conference was held 9- 12 August 1999 in Kuala Lumpur, Malaysia. The Malaysian Minister of Education Dato’ Sri Mohd and the president of the IIUM, Najib Tun Abdul Razak, officially opened the conference. Several ambassadors to Malaysia from Islamic countries, academicians, and prominent Islamic bankers attended the opening session. Over 200 delegates from more than 15 Muslim and non-Muslim countries attended the conference. Delegates represented academicians from private and public institutions of higher learning and officials from central banks and monetary authorities. The delegates included economists, corporate executives, government officials, officers involved in Islamic banking, investment bankers, fund managers, officials from zakat and waqf institutions, researchers in Islamic economics and related areas, and students of economics. Approximately 25 to 30 percent of the attendants were delegates representing countries other than Malaysia. Speakers and discussants included members of various universities and institutions such as the International Institute of Islamic Economics (Pakistan), the Islamic University of Palestine, Kausar University of Sciences (Pakistan), Rajshashi University (Bangladesh), King Abdel Aziz ... , number=4, journal=American Journal of Islam and Society, year=1999, month=Jan., pages=145–151